2014
DOI: 10.1021/cn500101j
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aβ but Not Tau is Related to Brain PiB Retention in Early Alzheimer’s Disease

Abstract: Recent advances in biomarkers provide the possibility of early or preclinical diagnosis of Alzheimer's pathology. Currently, decreased levels of Aβ-42 and increased levels of tau proteins in cerebral spinal fluid are considered reliable biomarkers of Alzheimer's disease (AD); however, little evidence exists for the use of amyloid and tau protein levels in the plasma as useful biomarkers. We investigated the potential use of plasma biomarkers to diagnose AD and explored their relationships with brain Aβ deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 57 publications
3
98
0
Order By: Relevance
“…The small increase in patients with AD was similar to that in a previous study on another cohort, 7 while other studies failed to detect differences between CNs, patients with MCI, and patients with AD 9 or found reduced plasma tau in patients with AD compared with CNs, patients with MCI, 4 or those with vascular dementia. 5 One group used an immunomagnetic reduction assay for plasma tau 8 with high separation between CNs and patients with AD (sensitivity and specificity >90% 3,6,8 ). Those findings await replication by independent groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The small increase in patients with AD was similar to that in a previous study on another cohort, 7 while other studies failed to detect differences between CNs, patients with MCI, and patients with AD 9 or found reduced plasma tau in patients with AD compared with CNs, patients with MCI, 4 or those with vascular dementia. 5 One group used an immunomagnetic reduction assay for plasma tau 8 with high separation between CNs and patients with AD (sensitivity and specificity >90% 3,6,8 ). Those findings await replication by independent groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous smaller studies failed to find associations between plasma tau and CSF tau 7 or PET Aβ biomarkers. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCD) may already occur in the stage of Aß42 accumulation in the absence of significant neurodegeneration 19 . Previous studies showed increased tau plasma levels in patients with AD [4][5][6] , in a group of patients with AD and mild cognitive impairment (MCI) due to AD 7 and in MCI due to AD 4 , but not in clinically classified MCI groups converting or not to AD during follow-up 5,6 . Taken together, our own result and these findings in literature indicate that plasma tau is a late marker of neurodegeneration, requiring substantial injury before increasing to abnormal levels at the transition from MCI to dementia stage of AD.…”
Section: Discussionmentioning
confidence: 97%
“…A blood test would fulfil all of these conditions in contrast to PET neuroimaging (expensive; exposure to ionizing radiation) and CSF analysis (invasive). Indeed, several previous studies have demonstrated increased tau plasma levels in patients with AD [4][5][6] , in a group of patients with AD and mild cognitive impairment (MCI) due to AD 7 and in MCI due to AD 4 . Much less is known whether increased tau plasma levels can already be detected in the pre-MCI stage of subjective cognitive decline (SCD).…”
mentioning
confidence: 99%